Does TQM influence employees' job satisfaction? an empirical case analysis - Ooi, K. B.; Abu Bakar, Nooh; Arumugam, V.; Vellapan, L.; Loke, A. K. Y. (Emerald Group Publishing Limited, 2007)
This paper seeks to examine employees' perceptions of TQM practices and its impact on job satisfaction within a large Malaysian outsourced semiconductor assembly and test (OSAT) organization. Despite extensive research on TQM practices, none examines this scope of investigative study. Therefore, the proposed model was developed with the intention of examining this relationship.